Simple quantum circuit for pattern recognition based on nearest mean classifier - Mahmoud Ahmed, Gharib Subhi; Messikh Azeddine, Azeddine (IIUM Press, 2016)
Machine learning plays a key role in many applications such as data mining and image recognition. Classification is one subcategory under machine learning. In this paper we propose a simple quantum circuit based on the nearest mean classifier to classified handwriting characters. Our circuit is a simplified circuit from the quantum support vector machine [Phys. Rev. Lett. 114, 140504 (2015)] which uses quantum matrix inverse algorithm to find optimal hyperplane that separated two different classes. In our case the hyperplane is found using projections and rotations on the Bloch sphere.